Significance of Plasma Adenosine in the Antiplatelet Activity of Forskolin: Potentiation by Dipyridamole and Dilazep - Agarwal, Kailash C; Zielinski, Beth A; Maitra, Ranjan S (Thrombosis and Haemostasis, 1989)
Forskolin, a plant (Coleus forskohlii) diterpene, inhibits ADP- induced (human: IC50, 2.3±1.0 μ;M; rat: IC50, 1.2±0.5 μM) and collagen-induced (human: IC50, 2.4±1.2 μM; rat: 0.6±0.2 μM) platelet aggregation in human and rat platelet-rich plasma (PRP). Human blood levels of adenosine (Ado) are low (100-300 nM) as compared to levels in rat plasma (7.55 ± 0.51 μM). Ado is a natural antiplatelet and vasodilatory agent produced by vascular endothelium, heart and other body tissues. If the plasma Ado is degraded by pretreatment of PRP with adenosine deaminase (ADA), forskolin inhibition on platelet aggregation is reduced by 2-4 fold both in human and rat blood. On the other hand, if the physiological steady state levels of Ado are maintained by collecting the blood in the presence of the inhibitors of ADA (2’-deoxycoformycin, dCF, 5 μM) and Ado uptake (dipyridamole, 10 μM or dilazep, 2 μM), forskolin inhibition (IC50, 3.2 μM) on platelet aggregation in human PRP is potentiated by 20-40 fold (IC50, 0.075-0.15 μM). Similar potentiated forskolin effect (IC50, 0.53 μM) is seen if the ADA-treated human PRP is replenished with a low level of Ado (50 nM) after ADA inactivation by dCF and Ado-uptake blockade by dilazep. If the plasma is replenished with a higher concentration of Ado (300 nM), greater potentiation is seen (IC50, 0.23 μM). Forskolin is 2-4 fold more inhibitory in rat PRP than in human PRP, partially due to the presence of higher levels of Ado in the rat plasma. These studies demonstrate an important role of plasma Ado in the antiplatelet activity of forskolin and this effect can be greatly potentiated by the clinically used drugs, dipyridamole and dilazep.
Keywords: Platelet; Forskolin; Adenosine; Dipyridamole; Dilazep